Pemikiran Pendidikan Islam Perspektif Ibnu Miskawaih - Siti Masyfufah; Muhammad Syaifuddin (DIMAR: Jurnal Pendidikan Islam, 2024)
Education is a very important part of human life. In the world of Islamic education, there are many educational figures who have succeeded in giving birth to great ideas that are still being used today, one of which is Ibn Miskawaih. The discussion of Ibn Miskawaih's Islamic education thought is very important to be studied more deeply in order to add insight and knowledge. This research uses library research method. The data sources in this research are journals, articles, websites, books, and various other information media. The data analysis technique used is content and data analysis. The problems to be answered in this study are (1) Who is Ibn Miskawaih? And (2) How is Islamic Education Thought according to Ibn Miskawaih? The results showed that Ibn Miskawaih was the most famous Islamic scientist and the first to write moral philosophy, he was also the secretary of Amirul-Umara Adhud-Daulah of the Buwaihi daulat in Baghdad, concurrently the head of the Bait al-Hikam library, a moralist, the father of Educational Psychology, a Muslim philosopher who focused his attention on Islamic ethics, historian, physician, scientist and writer. The basis of Islamic education according to Ibn Miskawaih is sharia and soul. The purpose of education according to Ibn Miskawaih is the achievement of moral glory, as well as achieving goodness and happiness. The function of education according to Ibn Miskawaih is as a means of socializing individuals, as well as humanizing humans (humanization).